Campus Canopy, 1937-12-11 - The Campus Canopy, The Georgia State Woman's College (Georgia State Womans College, 1937)
Outstanding Seniors To Be Elected -- Tournaments Bring Kappa-Lambda Sports Activities To Class -- College Plans 25th Yule Festival -- Alumnae Give Fountain
Georgia State Womans College Student Newspaper
Keywords: Valdosta State University -- Periodicals